Aberrant activation of the mentalizing brain system during eye gaze discrimination in bipolar disorder. (30th September 2021) - Tso, Ivy F.; Burton, Cynthia Z.; Lasagna, Carly A.; Rutherford, Saige; Yao, Beier; Peltier, Scott J.; Johnson, Timothy D.; McInnis, Melvin G.; Taylor, Stephan F.
Highlights: Social dysfunction in bipolar disorder (BD) may be due to altered mentalizing. Individuals with BD showed reduced activation in the mentalizing brain system. Aberrant activity of the mentalizing system was associated with poorer cognition/social cognition. Abstract: Bipolar disorder (BD) is associated with a range of social cognitive deficits. This study investigated the functioning of the mentalizing brain system in BD probed by an eye gaze perception task during fMRI. Compared with healthy controls ( n  = 21), BD participants ( n  = 14) showed reduced preferential activation for self-directed gaze discrimination in the medial prefrontal cortex (mPFC) and temporo-parietal junction (TPJ), which was associated with poorer cognition/social cognition. Aberrant functions of the mentalizing system should be further investigated as marker of social dysfunction and treatment targets.